Two Steps for Improving Reduced Graphene Oxide/Activated Durian Shell Carbon Composite by Hydrothermal and 3-D Ball Milling Process for Symmetry Supercapacitor Device - Nantikron Ngamjumrus; Kanyapak Silakaew; Somphob Thompho; Chaval Sriwong; Chesta Ruttanapun (My University, 2023)
Durian shell waste was used to fabricate activated carbon (AC) using a hydrothermal process and three-dimensional (3-D) ball milling. Reduced graphene oxide (rGO) was composited with activated durian shell carbon (DC) to enhance the electrochemical properties for fabricating a supercapacitor (SC) device. Scanning electron microscopic (SEM) examination of the AC from hydrothermally processed durian shell carbon (AC–HDC) and AC–HDC that was 3D ball milled for 15 min (rGO/AC–HDC–3D15M) showed compacted and uniformly distributed particles with good porosity. The rGO/AC–HDC–3D15M sample exhibited high specific surface area (SSA) using the Brunauer–Emmett–Teller (BET) methodology, 2311 m2/g, and an average pore size of 1.88 nm. Electrochemical results showed that the rGO/AC–HDC–3D15M sample had the highest specific capacitance (Cs) of 545.78 F/g, power density (Pd) of 260.834 W/kg and energy density (Ed) of 60.834 Wh/kg. A coin cell SC device using an rGO/AC–HDC3D15M electrode with a 3M KOH electrolyte exhibited a high Cs of 65.585 F/g with a high energy density of 5.123 W h/kg and power density of 47.286 W/kg. Thus, the novelty of this manuscript is that (1) the structure of the rGO/AC–HDC–3D15M composite could promote fast ionic and electronic migration during charging and discharging and (2) a rGO/AC–HDC–3D15M composite, which showed electric double-layer capacitor (EDLC) could produce a positive synergistic effect for efficient electrochemical reactions. Moreover, the high surface area of the rGO/AC–HDC–3D15M composite may mitigate the volume expansion of electrodes during cycling. Thus, this work shows that an rGO/AC–HDC–3D15M composite prepared using a hydrothermal process with 3-D ball milling can show enhanced electrochemical performance for the fabrication of an EDLC supercapacitor device.
Keywords: Power density; Specific surface area; Supercapacitor Materials and Fabrication